Model Experiments for Floating Stability of Self-Elevating Platform and Assessment Based on Theory of Structural Stability - Toma, Shouji (Transactions on Engineering and Computing Sciences, 2024)
A self-elevating platform (referred to as SEP hereafter), used as a pier, capsized during construction work at sea in March 2014. The structural characteristics of the SEP include a notably high center of gravity due to its long legs and a large rectangular plane, resulting in a shallow draft, which significantly differs from conventional vessels. While the stability of floating bodies is typically assessed using metacentric height and restoring moment curves based on conventional ship algorithms, it is essential to ascertain whether the same principles can be applied to the SEP, given its distinct structural features. In this study, an evaluation method based on structural stability theory, distinct from ship algorithms, was validated through model experiments. An analysis of overturning, based on structural stability theory previously employed for pile drivers on land, was conducted using the experimental results. As a result, it was discovered that both ship algorithms and structural stability theory essentially serve the same purpose in assessing the floating stability of SEP.